ANALISA YURIDIS TERHADAP PENARIKAN KENDARAAN BERMOTOR OLEH KREDITUR - Adrianus Sijabat; Firdaus '; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
A covenant is an event in which there is a promise to another person or two people to promise each other to carry out a thing. Default means not fulfilling what is required as what has been specified in the engagement. The non-fulfillment of obligations by the debtor is caused by two possible reasons, namely due to the debtor's mistake, whether intentionally or unfulfilled or negligent and because of overmacth, the force majeur may be due to human circumstances and influenced by natural conditions. Based on this understanding, the authors formulate two formulation of the problem, namely: First, Why the debtor is negligent in fulfilling the obligations as a debtor so that the creditor withdraw the debtor vehicle. Second, how the mechanism of motor vehicle withdrawal by the creditor for negligence or not carried out the debtor's liability to the creditor. The type of research or approach used by the author is normative legal research. Normative legal research is a legal research conducted by examining library materials or secondary data only. Because making the literature as the main focus of this research, the data source used, primary data, secondary data, and tertiary data, technical data collection in this study with literature study then by analyzing and processing the data qualitatively and generate descriptive data and then take the conclusion deductively. From the research results of the problem there are three main things that can be concluded, namely: First, Causes of Negligence Debtor Conducting Obligation As A Debtor. Second, Mechanism of Motor Vehicle Withdrawal by Creditor for Negligence or Not Performed Debtor Obligation To Creditor.Keywords : Agreement, , Withdrawal of Motor Vehicles